Pengaruh Identitas Merek, Harga, Dan Word Of Mouth Terhadap Keputusan Pembelian Produk - Rorlen; Ekadjaja, Margarita; Eric Adiwijaya; Elizabeth Christinio Puspita (Jurnal Ekonomi, 2023)
Brand identity needs to have a resonance with customers, the right price and marketing strategy can make customers try to buy or become loyal customers. This study analyzes the factors that influence customer decisions in purchasing products by adopting variables in marketing: brand identity, price, and word of mouth, and then analyzes whether they have some significant effect to put on purchasing decisions. The research of data was obtained from customers of Mixue products who are domiciled in the Bandung area. The results of data processing through the PLS-SEM application show that price and brand identity have a positive but not significant effect on purchasing decisions, while word of mouth has a significant positive influence on purchasing decisions. This shows that currently the word of mouth marketing strategy is more effective in getting customers or buyers.